Pengaruh E-service Quality, Brand Trust, dan Perceived Value terhadap Loyalitas Pelanggan Shopeefood (Studi Kasus pada Mahasiswa di Kota Malang) - Khasanah, Nur Munna Sakbannia Uswatun; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The surge in smartphone and internet usage in Indonesia has spurred the widespread adoption of digital technology in daily life. Among the youth, particularly university students, online food delivery services have become increasingly popular. Capitalizing on this trend, Shopee launched ShopeeFood in 2020, swiftly establishing itself as one of the top three platforms in the market. However, despite its rapid success, ShopeeFood has faced criticism over service quality issues. This study aims to analyze and evaluate the influence of e-service quality (X1), brand trust (X2), and perceived value (X3) on ShopeeFood customer loyalty, both partially and simultaneously. This research is an explanatory study employing a quantitative approach, with a sample consisting of 95 university students in Malang City. The research methodology utilized multiple linear regression analysis with SPSS 27 as the analytical tool. The results indicate that simultaneously, e-service quality, brand trust, and perceived value have a significant influence on customer loyalty. Partially, brand trust and perceived value have a significant positive influence on customer loyalty, whereas e-service quality does not have a significant partial effect on customer loyalty.  Keywords: E-Service Quality, Brand Trust, Perceived Value, Customer Loyalty, ShopeeFood